Factors Associated with Publication of Research Projects from a Canadian Master of Science Degree Programme in Physical Therapy. - McEachern, Brittany M.; Winningham, Ian; Wood, Kevin; Tang, Jack; VanDerWeide, Tim; O'Brien, Kelly K.; Salbach, Nancy M. (Physiotherapy Canada)
Purpose: The purpose of this study was to describe the nature and extent of publications and to evaluate whether lead advisor role and experience, data collection tool, sample size, and research topic predict publication for research projects completed as part of a Canadian Master of Science in Physical Therapy (MScPT) programme. Method: We conducted a quantitative, cross-sectional, retrospective review of projects completed between 2003 and 2015 and confirmed publication status through citations of published work, a literature search, and a survey of advisors. We used descriptive statistics to describe the nature and extent of publications and logistic regression to analyze potential predictor variables. Results: Between 2003 and 2015, 44.5% of the 218 projects completed were associated with at least one peer-reviewed journal publication, and there was a seven-fold increase in annual publication rate. Projects led by a scientist or researcher ([OR] = 3.09; 95% CI: 1.15, 8.35), qualitative projects with 10 or more participants ([OR] 6.22; 95% CI: 1.96, 19.78), and quantitative projects with more than 50 participants ([OR] = 2.29; 95% CI: 1.14, 4.63) were associated with an increased likelihood of publication. Conclusions: MScPT research is published at a moderate rate, and annual publication rates increased between 2003 and 2015. Encouragement to obtain adequate sample sizes and additional support for clinician-led projects may enhance publication rates and, ultimately, bridge gaps in research-to-practice integration.